2006
DOI: 10.1007/s00424-006-0073-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular properties of P2X receptors

Abstract: P2X receptors for adenosine tri-phosphate (ATP) are a distinct family of ligand-gated cation channels with two transmembrane domains, intracellular amino and carboxy termini and a large extracellular ligand binding loop. Seven genes (P2X(1-7)) have been cloned and the channels form as either homo or heterotrimeric channels giving rise to a wide range of phenotypes. This review aims to give an account of recent work on the molecular basis of the properties of P2X receptors. In particular, to consider emerging i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
142
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(152 citation statements)
references
References 165 publications
(243 reference statements)
3
142
0
7
Order By: Relevance
“…Aromatic amino acids are associated with recognition of adenine nucleotides in many ATP-binding proteins and are proposed to bind the adenine ring [5,75]. In addition, certain histidine residues within the protein can regulate P2X function [2,5]. It has been reported that glycine residues enhance flexibility in the extracellular loop, raising the possibility that they are involved in conformational changes in P2X receptors upon agonist binding [2,[76][77][78].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Aromatic amino acids are associated with recognition of adenine nucleotides in many ATP-binding proteins and are proposed to bind the adenine ring [5,75]. In addition, certain histidine residues within the protein can regulate P2X function [2,5]. It has been reported that glycine residues enhance flexibility in the extracellular loop, raising the possibility that they are involved in conformational changes in P2X receptors upon agonist binding [2,[76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, certain histidine residues within the protein can regulate P2X function [2,5]. It has been reported that glycine residues enhance flexibility in the extracellular loop, raising the possibility that they are involved in conformational changes in P2X receptors upon agonist binding [2,[76][77][78]. Swapping fragments and point mutations in the extracellular loop between rat and mouse P2X 7 receptors also demonstrated that amino acid residues in the ectodomain of the P2X 7 receptor are involved in the differential sensitivity to agonists between species [79].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the P2X 1 receptor is also desensitized, and this occurs very quickly and requires lower concentrations of nucleotides than for the metabotropic receptor P2Y 1 [95,96]. The physiological implications of P2X 1 desensitization are still not well understood but might be related to the need to confine thrombus growth to the site of a lesion and prevent uncontrolled extension of the platelet aggregates.…”
Section: Desensitizationmentioning
confidence: 99%